Ekosistem Perairan Payau: Struktur, Komponen, Dan Peran Ekosistem Dalam Mendukung Biodiversitas Pesisir - Gea, James Hendrafor; Telaumbanua, Andika Taufik Perdamaian (Jurnal Perikanan dan Kelautan, 2025)
Brackish water ecosystem is a transition system between fresh water and sea that plays an important role in supporting biodiversity and the lives of coastal communities. This study aims to identify biotic and abiotic components in brackish waters, as well as to examine their ecological and social roles. The observation method was carried out in Muara Indah, North Gunungsitoli, with a direct observation approach. The results show that this ecosystem is inhabited by mangrove vegetation such as Rhizophora apiculata and Avicennia marina, as well as fauna such as Scylla serrata and Hemiramphidae. The abiotic components observed include moderate salinity, muddy substrates, and calm water flow. This study emphasizes the importance of sustainable management of brackish water ecosystems that are vulnerable to human activities.